2020
DOI: 10.17161/jis.v13i1.11676
|View full text |Cite
|
Sign up to set email alerts
|

“She is the Best Female Coach”: Female Swimming Coaches’ Experiences of Sexism

Abstract: Sport participation for women and girls is at an all-time high in the United States, but women are still widely underrepresented in leadership positions and coaching (Acosta & Carpenter, 2014). Women hold approximately 50% of head coaching positions of women’s teams in the National Collegiate Athletic Association, and only 18% of the head coaching positions of women’s swimming and diving teams (LaVoi & Silva-Breen, 2018). Numerous barriers have been identified through previous research on the factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Additionally, many of the multilevel barriers and supports identified in the present study have been similarly documented in other research conducted internationally 3,32,33 and across different sporting codes (e.g. NCAA 18,34,35 ). Ongoing efforts to target such barriers (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, many of the multilevel barriers and supports identified in the present study have been similarly documented in other research conducted internationally 3,32,33 and across different sporting codes (e.g. NCAA 18,34,35 ). Ongoing efforts to target such barriers (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…It is important to note that intersectionality also includes the social relation between race, ethnicity, sexual orientation, class, and disability (Burton, 2015). Research regarding women in sport leadership has confirmed additional barriers for intersecting identities, such as parental status/motherhood (Siegele, Hardin, Smith, & Taylor, 2020) and sexual orientation (Walker & Melton, 2015). However, this study's focus is on gender and ethnicity.…”
Section: Purpose and Rationalementioning
confidence: 86%
“…Research has examined the challenges women encounter while trying to gain entrance into the collegiate athletics profession (Hardin et al, 2017;Siegele et al, 2020;Taylor et al, 2018). Hardin and colleagues (2017) described the glass door concept as an extension of the glass ceiling.…”
Section: Discussionmentioning
confidence: 99%